Tracer Study as an Instrument to Measure the Socio-Religious Impact of PTKI Graduates - Salamah Agung; Arief Subhan; Ari Lathifah (Mimbar Agama Budaya, 2025)
Islamic Higher Education Institutions (PTKI) play a pivotal role not only as centers of academic excellence but also as cultural brokers responsible for maintaining Islamic moderation and ethical values in society. However, measuring the socio-religious impact of PTKI graduates in the public sphere remains a significant challenge; current data shows that only 16.6% of PTKI alumni are traceable. This gap is largely due to the absence of a comprehensive tracer study model tailored to the unique socio-religious mission of PTKI. Using a qualitative descriptive approach, this study analyzes tracer study documents and interviews key informants from career centers across Indonesian higher education institutions. The findings reveal that current tracer implementations are often heavily administrative and structurally constrained. Therefore, this study recommends a robust, integrated tracer study management model for PTKI—encompassing clear national policies, institutional support, and synergistic IT data systems. By establishing this infrastructure, PTKI can utilize the tracer study not merely as an administrative tool for accreditation or employment tracking, but as a strategic instrument to accurately measure the socio-religious impact, ethical contributions, and cultural relevance of its graduates in the wider community.